Review-Mn4+-Activated Red and Deep Red-Emitting Phosphors - Adachi, Sadao (ECS journal of solid state science and technology, 2019)
Mn4+-activated phosphors are a new class of non-rare earth phosphors and are alternative to commercial Eu2+-activated nitride/oxynitride phosphors with growing interest in various applications. In this review article, the structural and photoluminescence (PL) properties of various Mn4+-activated phosphors have been discussed. The host materials considered here can be roughly classified into five groups; fluorides, oxides, oxyfluorides, and two fluorine compounds. Phosphors of each group can also be classified into totally eleven subgroups from their different PL spectral features, e.g., whether an appearance of the zero-phonon line (ZPL) emission peak or not. The ZPL emission and absorption energies of the Mn4+ ions have been determined from the PL and PL excitation spectra using the Franck−Condon analysis method within the configurational-coordinate (CC) model. These results are used to obtain reliable phosphor parameters, i.e., the crystal-field (Dq) and Racah parameters (B and C), of the Mn4+ ions in the various host materials. The PL intensity vs temperature data, together with those of the luminescence lifetimes, are modeled on the basis of the CC model, and an excellent agreement has been achieved if not only the optical phonon but also the acoustic phonon contribution is taken into consideration in the conventional thermal quenching model. Effects of the hydrostatic pressure and dopant concentration on the PL spectral features are also discussed. Finally, key properties of the Mn4+-activated phosphors are discussed for use of such red and deep red-emitting phosphor systems in warm w-LED and indoor plant cultivation applications.